Nanocomposite Thin Film TiO2/CdS Electrodes Prepared by Thermal Evaporation Process for Photovoltaic Applications - Chien, Dang Tran; Long, Pham Duy; Hoi, Pham Van; Chi, Le Ha (Communications in Physics, 2011)
The incorporation of cadmium sulfide (CdS) into TiO2 nanoparticle thin films was investigated. The nanoparticle TiO2 thin film onto an indium doped–tin oxide (ITO) substrate was deposited by Electron Beam Deposition (EBD) combined with thermal process. Then a CdS thin film was vacuum-deposited onto the pre-deposited TiO2 film by a thermal evaporation technique. The obtained TiO2/CdS was characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM). The TiO2/CdS nanocomposite film was used in a photo-electrochemical (PEC) cell as a working electrode and a platinum electrode as a counter electrode. The electrolyte solution contains 1 M KCl and 0.1M Na2S. The results show that the cell with TiO2/CdS composite film electrode has significantly improved photoelectric capability in comparison with that of the pure TiO2 thin films.